Frequency of congenital hypothyroidism in new born admitted with neonatal jaundice at tertiary care hospital peshawar - Ahad, Abdul; Bibi, Romana; Rehman, Sijad Ur; Shah, Majid Ali; Ullah, Matea; Shahinda (Journal of Rawalpindi Medical College, 2023)
Neonatal jaundice is a common disorder worldwide affecting 30-70% of newborn infants. Severe neonatal jaundice and its progression to kernicterus is a leading cause of death and disability among newborns in poorly-resourced countries. OBJECTIVES: To determine the frequency of congenital hypothyroidism in new born admitted with neonatal jaundice at tertiary care hospital Peshawar. METHODOLOGY: Settings: removed for blind review Duration: Period of 1 year from January 2020- January 2021. Study Design: Descriptive (cross sectional) study. Results: In our study 489 mothers 386(79%) mothers were in age range 18-30 years while 103(21%) mothers were in age range 31-40 years. 279(57%) babies were male and 210(43%) babies were female. 303(62%) newborns had maternal gestation age ≤38 weeks and 186(38%) neonates had gestation age >38 weeks. 352(72%) newborns had duration of jaundice ≤14 days and 137(28%) newborns had duration of jaundice >14 days. Birth weight was analyzed as 200(41%) newborns had birth weight ≤2.5 kg and 289(59%) newborns had birth weight >2.5 kg. 15(3%) Mothers had positive history of hypothyroidism while 474(97%) mothers had negative history of hypothyroidism . 24(5%) mother had positive history of anti-thyroid drug intake while 465(95%) mothers had negative history of anti-thyroid drug intake. 5(1%) newborn had congenital hypothyroidism while 484(99%) newborn didn’t had congenital hypothyroidism. Conclusion: Our study concludes that the frequency of congenital hypothyroidism was 1% in new born admitted with neonatal jaundice at tertiary care hospital Peshawar. Key words: Hypothyroidism, Jaundice, kernicterus, bilirubin, morbidity, anti-thyroid drugs.